Toward automated tomato harvesting system integration of haptic based piezoresistive nanocomposite and machine learning - Azhari, Saman; Setoguchi, Takuya; Sasaki, Iwao; Nakagawa, Arata; Ikeda, Kengo; Azhari, Alin; Hasan, Intan Helina (IEEE, 2021)
Carbon nanotubes (CNT)/polydimethylsiloxane (PDMS) have been investigated as potential materials for tomato-harvesting applications. The current-voltage (I–V) and current time (I–t) properties, as well as tomato hardness measurement and support-vector machine learning, were used to determine the performance of the sensor with respect to sensitivity, response time, accuracy, and detection limit of the nanocomposite. The data suggested an accurate (± 5.2%) measurement in a low-weight region of tomato. Narrowing of the I–V hysteresis curve towards a higher weight region was observed as a result of the increase in electron pathways. The fabricated sensor displayed a higher sensitivity (15 mV $/ μ \text{m}$ ) than the commercial sensor (1 mV $/ μ \text{m}$ ). In addition, machine learning of the resistance–displacement curve data yielded an average accuracy level of 0.67 when tested using acquired data.